2014
DOI: 10.2478/s11536-013-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of exposure to formaldehyde in dental materials

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Among these 13 (43.3%) were positive to formaldehyde (tested 0.1% in water) compared to 9 (18.8%) of 48 nonexposed. Formaldehyde was considered a stronger skin sensitizer than glutaraldehyde (tested 0.2% in pet), to which 8 (26.7%) dental professionals and 11 (22.9%) from the control group reacted [1]. A study performed in India in 2010 using a pretested self-administered questionnaire showed that 16% of 163 dentists (73% male and 27% female) reported allergy to latex gloves [23].…”
Section: Dental Personnelmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 13 (43.3%) were positive to formaldehyde (tested 0.1% in water) compared to 9 (18.8%) of 48 nonexposed. Formaldehyde was considered a stronger skin sensitizer than glutaraldehyde (tested 0.2% in pet), to which 8 (26.7%) dental professionals and 11 (22.9%) from the control group reacted [1]. A study performed in India in 2010 using a pretested self-administered questionnaire showed that 16% of 163 dentists (73% male and 27% female) reported allergy to latex gloves [23].…”
Section: Dental Personnelmentioning
confidence: 99%
“…Dentists, dental nurses and assistants, and dental laboratory technicians suffer predominantly from irritant contact dermatitis. While in the last 30-35 years, allergic contact dermatitis to acrylates, rubber products, disinfectants, detergents, and formaldehyde [1] was seen to be more frequent, but to a lesser degree, the equivalent of this in the mouth, allergic contact stomatitis, was a rare phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, advances in dental material science have promoted the expectations of dentists and patients about the safety and efficiency of dental products [1]. Nowadays, there are several kinds of acrylic resins in the dental market, and each of them shows some advantages and disadvantages [2].…”
Section: Introductionmentioning
confidence: 99%
“…[23] In our previous studies, irritant and skin-sensitizing effects of formaldehyde among dental students exposed during their practical education were well documented. [2425] No studies were found in the available literature concerning the incidence of contact sensitization to formaldehyde among veterinary medicine students and lecturers.…”
Section: Introductionmentioning
confidence: 99%